TAZKIYATUN NAFS DAN PENCEGAHAN PSIKOSOMATIK SANTRI: RELASI JIWA-RAGA DALAM HIDUP PESANTREN : Indonesia - Zainabur Rahmah; Adam Abdillah; Ardenta Fawwaz Anarya; Alan Adi Syahputra; Muhammad Amiruddin (PT. Sulthan Journal Publisher, 2026)
This study discusses the concept of tazkiyatun nafs as a process of spiritual purification in Islamic teachings and its role in preventing psychosomatic disorders among santri in Islamic boarding schools. This study is motivated by the importance of maintaining a balance between mental and physical health amid various psychological pressures experienced by santri, such as academic demands, environmental adaptation, and social dynamics within pesantren. The research employed a qualitative method using a literature study approach through the examination of Islamic literature and modern psychological theories. The findings indicate that the practices of tazkiyatun nafs, including dhikr, muhasabah, repentance, patience, and self-control, play an important role in maintaining the emotional and spiritual stability of santri. These practices function not only as forms of worship but also as efforts to control stress and anxiety that may trigger psychosomatic disorders. In addition, the religious and disciplined environment of pesantren supports the development of santri’s overall mental health. Therefore, the integration of Islamic spiritual approaches and modern psychology can become a preventive solution in maintaining the balance between the soul and the body of santri.